Monitoring Peroxides Generation During Model Wine Fermentation by Fox-1 Assay - Lissi-Gervaso, E; Aspee-Lamas, A (Elsevier Ltd, 2015)
The quality of wine is mainly determined during the alcoholic fermentation that gradually transforms the grape juice into wine. Along this process the yeast goes through several stressful stages which can affect its fermentative ability and industrial performance, affecting wine quality. Based on their actual application on industrial winemaking, commercial Saccharomyces cerevisiae strains (EC1118, QA23, VIN7 and VL3) were used. They were inoculated in batch laboratory fermentations in a model wine solution for evaluating the production of reactive oxygen species (ROS) during the yeast s alcoholic fermentation. For first time total hydroperoxides were determined by FOX-1 assay to follow ROS generation. The total hydroperoxides accumulated along the 10 days of fermentation peaked up to 10.0 μM in yeast EC1118, of which 1.3 μM was hydrogen peroxide (H2O2). The FOX-1 based analytical approach herein presented is a valuable tool for the quantification of ROS oxidative damage during winemaking. © 2014 Published by Elsevier Ltd.